2012
DOI: 10.1073/pnas.1204759109
|View full text |Cite
|
Sign up to set email alerts
|

Active DNA unwinding dynamics during processive DNA replication

Abstract: Duplication of double-stranded DNA (dsDNA) requires a fine-tuned coordination between the DNA replication and unwinding reactions. Using optical tweezers, we probed the coupling dynamics between these two activities when they are simultaneously carried out by individual Phi29 DNA polymerase molecules replicating a dsDNA hairpin. We used the wild-type and an unwinding deficient polymerase variant and found that mechanical tension applied on the DNA and the DNA sequence modulate in different ways the replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(116 citation statements)
references
References 43 publications
6
108
2
Order By: Relevance
“…The mutant protein paused extremely rarely on all DNA substrates studied, strongly suggesting that the transient (and presumably failed) recognition of Chi-like sequences momentarily stalls the complex on DNA. Pausing of DNAunwinding enzymes has also been attributed to the unfolding of kinetic barriers dependent on sequence (25,26,35). However, the experiment with the mutant AddAB complex excludes the possibility that the pauses are caused by high GC content, as this would be expected to directly affect the AddA helicase motor as opposed to the Chi-scanning module.…”
Section: Discussionmentioning
confidence: 97%
“…The mutant protein paused extremely rarely on all DNA substrates studied, strongly suggesting that the transient (and presumably failed) recognition of Chi-like sequences momentarily stalls the complex on DNA. Pausing of DNAunwinding enzymes has also been attributed to the unfolding of kinetic barriers dependent on sequence (25,26,35). However, the experiment with the mutant AddAB complex excludes the possibility that the pauses are caused by high GC content, as this would be expected to directly affect the AddA helicase motor as opposed to the Chi-scanning module.…”
Section: Discussionmentioning
confidence: 97%
“…Tension on the template strand of the DNA destabilizes the PTS and triggers transfer of the DNA 3 0 end to the exo site. The destabilizing effect of force on the PTS appears to be similar to that of incorporating an erroneous base, and has previously been used to study exonucleolysis by DNAp (8)(9)(10). It also has been shown that the apparent rate of polymerization goes down as tension increases up to~35 pN (8), after which DNAp seems to exclusively perform exonucleolysis (10,11).…”
Section: Introductionmentioning
confidence: 94%
“…Recently, we described a series of single molecules experiments designed to understand the molecular mechanism used by the Phi29 DNAp to unwind the DNA and to couple the processes of DNA replication and unwinding 5,6 . To this end, using optical tweezers, we measured the combined effect of mechanical force, favoring the DNA unwinding reaction and, DNA sequence on the real time kinetics of single polymerases molecules replicating through a DNA hairpin.…”
Section: The Pause Behaviour Modulates the Average Replication Vementioning
confidence: 99%